Implementation of Halal Certification on Food Products for Consumer Protection Special Study: Processed Marshmallow Food Products - Deviana Putri Septia Ningrum; Veni Vebriyanti; Siti Aisah Hidayatul Hasanah; Noval Firdaus; Lailatul Maghfiroh (Penerbit Hellow Pustaka, 2025)
The growth of the processed food industry in Indonesia shows a significant upward trend, in line with the high consumption of imported products such as marshmallows, which are popular with the public, especially among children and adolescents. However, basic marshmallow ingredients, such as gelatin, are often derived from animal sources whose halal status is unclear, raising concerns among Muslim consumers. Therefore, the implementation of halal certification is a crucial instrument in ensuring the safety and halal status of food products while simultaneously protecting consumer rights. This study aims to analyze the application of halal certification to processed marshmallow products and assess its effectiveness in protecting Muslim consumers. This study uses a qualitative approach with a literature review method to understand in-depth the implementation of halal certification in processed food products, particularly marshmallow products, in the context of consumer protection. This approach was chosen because the research focuses on analyzing theories, concepts, regulations, and previous research results relevant to the topic under study. The results show that the implementation of halal certification in marshmallow products is not optimal due to limited raw material transparency and low awareness of the importance of halal certification among small producers. However, for certified producers, halal certification can increase consumer trust and strengthen the product's position in the market. Thus, halal certification plays an important role as a consumer protection instrument that needs to be strengthened through ongoing socialization and supervision.